National Research and Extension Agenda for Agricultural Safety and Health Assessment. Issue 3 (3rd July 2018) - Gorucu, Serap; Murphy, Dennis; Yoder, Aaron; Pate, Michael
ABSTRACT: This brief report for the Journal of Agromedicine presents key findings of a systematic review of scholarly products produced between 2004 and 2015 associated with agricultural safety and health priority areas. This brief report is derived from "A review of the National Research and Extension Agenda for Agricultural Safety and Health". The purpose of this report is to provide a synopsis of extension and research safety efforts and provide recommendations for extension. The scholarly products were classified into three main groups: peer-reviewed journal articles, technical conference papers, and educational products. It was found that more scholarly products were produced in the priority areas in more recent years, and more educational products were produced than peer-reviewed journal articles. Land-grant universities alone produce almost one-half of the total scholarly products within the priority areas.